2022
DOI: 10.1140/epje/s10189-022-00244-9
|View full text |Cite
|
Sign up to set email alerts
|

Studying the aging of Laponite suspensions using extensional rheology

Abstract: The effect of aging on the break-up dynamics of Laponite suspensions was studied in an extensional geometry. It was found that samples of increased age undergo stronger necking at the midpoint. The thinning of samples, driven purely by motion of the plates, was compared with standard shear rheology to understand how the dynamics are related to the sample properties. The Laponite suspensions exhibit a growing stress overshoot with monotonically decreasing yield strain as they age. However, it is shown that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…where N A is Avogadro's number,R g is the hydrodynamic radius of the PEO chains (R g � 0.022M w 0.583 Recent rheological experiments with Lap suspensions (C Lap = 3, 3.5 and 4 %, pH = 10) demonstrated that after an initial linear visco-elastic regime, the samples accumulate significant plastic deformations prior to the complete yielding of the sample. [58] During the aging the samples became slightly more brittle and the sample with high Lap concentration exhibited shear bands.…”
Section: Aging Effectsmentioning
confidence: 99%
“…where N A is Avogadro's number,R g is the hydrodynamic radius of the PEO chains (R g � 0.022M w 0.583 Recent rheological experiments with Lap suspensions (C Lap = 3, 3.5 and 4 %, pH = 10) demonstrated that after an initial linear visco-elastic regime, the samples accumulate significant plastic deformations prior to the complete yielding of the sample. [58] During the aging the samples became slightly more brittle and the sample with high Lap concentration exhibited shear bands.…”
Section: Aging Effectsmentioning
confidence: 99%